Relationship of Tijuana River Flow and Ocean Bacteria Counts and Emergency Department Diarrhea Cases - Jaya Jost; Conor Youngblood; Peter Jost; Roberto Medero (Western Journal of Emergency Medicine)
Introduction: The Tijuana River, which affects southern San Diego Beaches, is severely contaminated with untreated sewage. Exposure to pathogens can lead to various health problems, commonly gastrointestinal (GI) illnesses. We aimed to look for any relationship between Tijuana River flow rates and ocean pollution levels and levels of diarrhea at a nearby Emergency Department (ED). Methods: In this retrospective study that spanned the 2023 dry season and included Hurricane Hillary, we compared Tijuana River flow rates and fecal bacterial counts on the southern San Diego County coastline to the number of visits to a nearby ED, specifically a 225-patient sample size, with the chief complaint of diarrhea, a potential waterborne illness. Results: In late August of 2023, after Hurricane Hillary made landfall as a tropical storm in Baja California, Mexico, there was a large increase in the Tijuana River flow rate and a correspondingly significant increase in diarrhea cases at 3.25 times the mean, from a mean of 4.25 cases per week to 14 cases the week of Hurricane Hillary. Conclusion: We found a significant correlation between Tijuana River transboundary flow rates and Emergency Department case levels of diarrhea, a known waterborne illness, in the summer of 2023.